Application of the Simple Additive Weighting Method in the Decision Support System for Determining the Best Village Officials - Qubro, Baiq Ainurrahmi Imanda; Saikin, Saikin; Fahmi, Hairul (JISA(Jurnal Informatika dan Sains), 2025)
Performance evaluation of village officials in Bunut Baok Village is still carried out manually using assessment sheets, which often leads to subjectivity, unclear assessment aspects, and slow decision-making. These issues indicate the need for a Decision Support System (DSS) capable of providing objective and transparent evaluations based on measurable criteria. This study aims to develop a DSS using the Simple Additive Weighting (SAW) method to determine the best-performing village officials. Data were collected through observation and interviews with the Village Head and Village Secretary, involving 13 village officials as evaluation subjects. The dataset consists of five assessment criteria attendance, daily activity reports, output of activities, discipline, and service each represented through a linguistic scale (excellent, good, fairly good, poor) which was then converted into numerical weights for SAW processing. The results show that alternative A1 (Head of Gelogor Mapong Region) achieved the highest preference score of 0.938, indicating superior performance based on all evaluated criteria. The findings demonstrate that the SAW method effectively supports structured and transparent decision-making at the village governance level and can serve as a reference framework for future DSS implementations in local government environments.